Factors that affect the acceptance level of consumers in Malaysia towards environmental- friendly products / Norhayati Muhamad Mazlan - Muhamad Mazlan, Norhayati (Faculty of Business and Management, 2013)
Nowadays Malaysian governments and other related non-government organizations are moving towards encouraging local society to be more aware with environmental-friendly product and try to enhance their consumption patterns towards that kind of products. On the other hand, developed nations like European and Japanese are known for their high-concerns towards environmental issue. Therefore, researcher tries to find out what are the relevant factors that can affect the acceptance level of consumers in Malaysia towards environmental-friendly products. The aim of this paper is to identify contributing factors towards the acceptance of environmental-friendly products, to determine whether the price factor contribute towards the acceptance level of consumers in Malaysia, to determine whether the availability factor contribute towards the acceptance level of consumers in Malaysia and to determine whether the awareness factor contribute towards the acceptance level of consumers in Malaysia. This paper is devoted to revise the relevant literature regarding on the issue. This topic is divided into several areas which are the definition of environmental-friendly product, the acceptance level the role of price, the availability factor as well as the awareness factor. The researcher was using questionnaire as medium of collecting data from local consumers located around Kuala Lumpur as the appropriate respondents. It is in order to get the accurate result for next step of investigation which is analysing data through SPSS. From the responses of 30 respondents, the researcher will compute all the data so that the findings can be created. Furthermore, suitable recommendation will be concluded in this report.